Factors associated with type 1 diabetes treatment adherence in adolescents: scoping review - Angulo Landázury, Yully Vanessa (2023)
Diabetes Mellitus Type 1 is one of the chronic diseases with the highest prevalence in adolescence, it is a condition characterized by high levels of glucose in the bloodstream, consequent to pancreatic dysfunction, its approach depends on a variety of factors that adding to pharmacological treatment facilitate better metabolic control and disease exacerbation. Objective: to determine the factors associated with adherence to treatment of Type 1 Diabetes Mellitus (DM1) in adolescents, published in the scientific literature during the period 2017 to 2022. Method: a scoping review was performed following the five-stage approach, suggested by Arksey and O'Malley, as well as, using the PRISMA method. Main Results: 14 scientific articles were reviewed, which made it possible to determine that among the factors associated with adherence to DM1 treatment are those related to adolescent mental health, family support network, diet, sedentary habits, lack of schooling, social status and sleep habits. General Conclusion: adherence to treatment for Type 1 Diabetes (DM1) in the adolescent population depends on different factors such as depression and/or stress, inadequate diet, sedentary practices and certain socio-family dynamics of the individual, which, added to the evolutionary changes typical of adolescence, largely determine the control or complication of the disease.